Comparison of Antibacterial Effectiveness Tests Between Aloe Vera Gel (Aloe Vera L.) And Pure Kaliandra Honey (Calliandra Calothyrsus) On The Growth of Staphylococcus Aureus - Dzil Fikri; Atika N. Febrianti; Muhammad Fadhil (International Journal of Health and Pharmaceutical (IJHP), 2025)
Background: Aloe  vera (Aloe vera L) and honey (Calliandra calothyrsus)  have many benefits, especially in Indonesia, aloe vera and honey are also often used as drugs for various diseases because of their content which has many health benefits.  Objective: This study aims to determine the comparison between aloe vera (Aloe vera L)  and honey (Calliandra calothyrsus)  as an inhibitor of the growth of Staphylococcus aureus bacteria.Method: This study uses true experimental design  in microbiological test with post test only control group design. With the treatment of aloe vera gel (Aloe vera L) and kaliandra honey (Calliandra calothyrsus) and ciprofloxacin antibiotics as a positive control and aquades as a negative control against Staphylococcus aureus bacteria  to see antibacterial effectiveness using diffusion methods in thelaboratory.Results: The most effective variable was kaliandra honey (Calliandra calothyrsus) with concentrations of 50%, 75% and 100% with p values of 0.03, 0.01, and 0.03 respectively when compared to using aloe vera gel (Aloe vera L) with concentrations of 25%, 50%, 75% and 100% which obtained the results could not at all inhibit the growth of Staphylococcus aureus bacteria. Conclusions and Suggestions:  This research can be used as a theoretical basis, so that people can choose a more appropriate ingredient, namely kaliandra honey (Calliandra calothyrsus) rather than using aloe vera gel (Aloe vera L) to be used as herbal medicine by people who experience Staphylococcus aureus  bacterial infections. Other researchers are also advised to be able to use other variables or other types of aloe  vera (Aloe vera L) and honey from the nectar of other flowers to conduct similar studies.